2021
DOI: 10.1002/smtd.202101324
|View full text |Cite
|
Sign up to set email alerts
|

Flame‐Assisted Synthesis of O‐Coordinated Single‐Atom Catalysts for Efficient Electrocatalytic Oxygen Reduction and Hydrogen Evolution Reaction

Abstract: Single‐atom catalysts (SACs) exhibit intriguing performance in electrocatalysis owing to their maximized atom utilizations and unique electronic structures, but effective anchoring metal atoms with defined coordination structure on hierarchical integrated electrode remain a challenge. Herein, a fast and facial flame‐assisted strategy is developed to construct oxygen‐coordinated SACs on integrated carbon nanotube (CNT) arrays with promising applications in electrocatalysis. Density functional theory calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…Specically, the ethanol ame treatments only take a few seconds, and the loading mass can be readily controlled by regulating the number of repetitions, which is time-efficient and suitable for large-scale production. Although such ame treatments were previously utilized to grow carbon nanotubes on various substrates, 23,24 to the best of our knowledge, the growth of atmosphere-sensitive sulfur compounds has been scarcely achieved. In this work, by utilizing thioacetamide, the successful conversion of oxides to sulde/sulfates with high yield is demonstrated (the atomic S ratio of 6.43% in MSEI@Cu).…”
Section: Preparation and Characterization Of Msei@cumentioning
confidence: 99%
“…Specically, the ethanol ame treatments only take a few seconds, and the loading mass can be readily controlled by regulating the number of repetitions, which is time-efficient and suitable for large-scale production. Although such ame treatments were previously utilized to grow carbon nanotubes on various substrates, 23,24 to the best of our knowledge, the growth of atmosphere-sensitive sulfur compounds has been scarcely achieved. In this work, by utilizing thioacetamide, the successful conversion of oxides to sulde/sulfates with high yield is demonstrated (the atomic S ratio of 6.43% in MSEI@Cu).…”
Section: Preparation and Characterization Of Msei@cumentioning
confidence: 99%
“…SACs with the above structures have shown excellent electrocatalytic performance. [ 51–55 ] Compared with doping heteroatoms, recent reports have demonstrated that the coordination environment of carbon‐based SACs can be exactly controlled by exploiting the differences of various heteroatoms. [ 56–58 ]…”
Section: Introductionmentioning
confidence: 99%
“…SACs with the above structures have shown excellent electrocatalytic performance. [51][52][53][54][55] Compared with doping heteroatoms, recent reports have demonstrated that the coordination environment of carbon-based SACs can be exactly controlled by exploiting the differences of various heteroatoms. [56][57][58] Although some outstanding reviews have been provided on regulating the coordination environment of carbon-based SACs, [59][60][61][62] most of them have focused on the structures of active sites without describing the detailed methods and strategies involved.…”
Section: Introductionmentioning
confidence: 99%
“…The SMSI effect is significantly enhanced in the case of single-atom catalysts (SACs), which provide exceptional atom utilization efficiency. , It is well known that catalytic performance is controlled by the accessible surface area and intrinsic activity per active site, which has been shown to be maximized with the utilization of SACs. However, the synthesis of SACs for OER that do not contain carbon is still in its infancy, with not many developed preparation strategies for the Ir SACs, in particular in acidic media. Examples of synthetic strategies include an in situ cryogenic–photochemical reduction method (for Ir single-atom sites on NiFe oxyhydroxides), electrochemical methods (for Ir SAC on a nickel-iron sulfide nanosheet array substrate), co-electrodeposition methods (Ir SAC on ultrathin NiCo 2 O 4 nanosheets), chemical reduction method (Ir SAC on CoO x amorphous nanosheets with abundant surface absorbed oxygen; Ir SAC incorporated in Co-based hydroxide nanosheets), and thermal decomposition method (Ir SAC on the NiO matrix) .…”
Section: Introductionmentioning
confidence: 99%